2022
DOI: 10.3389/fonc.2022.912624
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Testis Antigen LDH-C4 in Tissue, Serum, and Serum-Derived Exosomes Serves as a Promising Biomarker in Lung Adenocarcinoma

Abstract: ObjectiveAs a cancer-testis antigen (CTA), human lactate dehydrogenase C4 (LDH-C4) enzyme protein encoded by the LDHC gene has been reported to be involved in the occurrence and development of various malignancies, while its expression and clinical significance in lung adenocarcinoma (LUAD) remain unclear. This study aims to investigate the expression of LDH-C4 in LUAD and its diagnostic and prognostic value.MethodsThe mRNA and protein levels of LDH-C4 in LUAD and adjacent normal tissues were analyzed based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Available bioinformatics analyses can be a powerful tool for identifying biomarkers and therapeutic targets related to tumour progression and treatment. Previous studies have shown that novel serum biomarkers, including serum exosomes ( 27 29 ) and serum CEA ( 30 33 ), are good predictors of prognosis in lung adenocarcinoma. In addition, serum biomarkers related to inflammatory response are also good predictors of lung adenocarcinoma prognosis ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Available bioinformatics analyses can be a powerful tool for identifying biomarkers and therapeutic targets related to tumour progression and treatment. Previous studies have shown that novel serum biomarkers, including serum exosomes ( 27 29 ) and serum CEA ( 30 33 ), are good predictors of prognosis in lung adenocarcinoma. In addition, serum biomarkers related to inflammatory response are also good predictors of lung adenocarcinoma prognosis ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pan-cancer expression of LDHC /LDH-C4 has been assessed, and the results of IHC based on high-throughput tissue microarray analyses suggest the highest positivity rate of LDH-C4 in LUAD (96.7%) ( 63 ), followed by breast cancer (BC) (91.55%) ( 36 ), and hepatocellular carcinoma (HCC) (55.84%) ( 37 ). LDHC is expressed in serum and serum exosomes of tumor patients, with serum LDHC positivity rates of 91.66%, 68%, and 65% in BC ( 36 ), HCC ( 37 ), and LUAD ( 63 ), respectively. Serum-sourced exosomal LDHC in BC and HCC also yield comparable positivity rates as those in the serum ( 36 , 37 ).…”
Section: Ldhc /Ldh-c4 and Tumorsmentioning
confidence: 99%
“…However, LDHC was a protective factor for prognosis in HNSCC and CESC ( Figures 3A, B ). In LUAD ( 63 ), LDH-C4 protein was significantly associated with TNM tumor status, and patients with high LDH-C4 expression had a worse prognosis than those with low/negative expression. Similar results were observed in HCC ( 37 ) and BC ( 36 ).…”
Section: Ldhc /Ldh-c4 and Tumorsmentioning
confidence: 99%
See 1 more Smart Citation